Implementasi Penggunaan Microsoft Teams sebagai E-Learning Platform dalam pembelajaran Bahasa Inggris berdasarkan E-tivities Model di SMA Negeri 2 Pati - Fatimah Dwi Pangestuti; Theresia Cicik Sophia Budiman; Fitri Yulianti (ELT in Focus, 2021)
The development of information and communication technology is helpful to teacher and students in teaching and learning process in the pandemic era. Technology can improve the quality of media for teaching and learning activities. E-learning is one example of innovation in education that is beneficial to facilitate the teacher and students in distance learning during Covid19 pandemic. This research is aimed to delineate the process of the implementation of Microsoft Teams as E-Learning platform in English learning based on e-tivities model in a public secondary high school in Semarang, and to find out the teacher and students’ perception toward the implementation process. This research used qualitative approach. The research participants include an English teacher in X MIPA 5 class and 36 students at X MIPA 5. The research used observation sheet and documentation to figure out the implementation of Microsoft Teams as E-Learning platform in English learning based on E-tivities model. Moreover, interview guideline and questionnaire were used to collect data related to students and teacher perception toward the implementation of the learning model. The results showed that five stages of e-moderating in e-tivities including access and motivation, online socialization, information exchange, knowledge constructions, and development stages were implemented by the teacher in English learning using Microsoft Teams. The teacher perception toward the implementation Microsoft Teams as E-Learning platform was that this application is beneficial with many features, so it can make it easier for the teacher to manage online teaching and learning during pandemic. In addition, the students perceived that implementing Microsoft Teams was more effective and flexible because it had complete features for learning, and thus using Microsoft Teams has a positive impact on online learning activities.